2008
DOI: 10.1262/jrd.20004
|View full text |Cite
|
Sign up to set email alerts
|

Fertility after Artificial Insemination Using a Soybean-Based Semen Extender in Sheep

Abstract: Abstract. The present study aimed to compare the fertility of ewes intrauterinally inseminated with frozen-thawed semen using a soybean-based semen extender (AndroMed) with those of ewes intrauterinally inseminated with frozenthawed semen using a Tris-based extender containing either egg yolk or BSA. Suffolk ewes (n=104) were treated with an intravaginal sponge containing 40 mg fluoroprogesterone acetate (FGA) for 12 days and an intramuscular injection of 500 IU equine chorionic gonadotropin to induce estrus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 23 publications
11
43
0
6
Order By: Relevance
“…Spermatozoa that are morphologically defective or have poor motility tend to have low success rate of oocyte fertilization. The decreased fertility rates of the L1, L3 and L6 groups compared to those observed in sperm that were frozen with egg yolk are consistent with findings from other authors [17,[19][20][21] . Those authors have observed a deleterious effect or a reduction in the fertility of semen frozen in the presence of soybean lecithin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Spermatozoa that are morphologically defective or have poor motility tend to have low success rate of oocyte fertilization. The decreased fertility rates of the L1, L3 and L6 groups compared to those observed in sperm that were frozen with egg yolk are consistent with findings from other authors [17,[19][20][21] . Those authors have observed a deleterious effect or a reduction in the fertility of semen frozen in the presence of soybean lecithin.…”
Section: Discussionsupporting
confidence: 92%
“…Most semen extenders contain egg yolk and skim milk as sources of lipoprotein that protects sperm cells from cold shock and other damage [9,10] . However, the possible disadvantages of using egg yolk, including its potential to be a cause of allergic reactions, the risk of bacterial contamination and its variable effect on semen have been ÜSTÜNER, ALÇAY, NUR SAĞIRKAYA, SOYLU Effect of Egg Yolk and Soybean ... reported [7,9,11,17] . On the other hand, soybeans contain a high component of low-density lipoprotein, e.g., lecithin or egg yolk-like lecithin [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first to find the AndroMed ® extender preferable were Aires et al (2003). In accord with the present findings, others confirmed this assessment for various ruminant species (Herold et al, 2003;Amirat et al, 2005;Janett et al, 2005;Akhter et al, 2010;Mohan and Atreja, 2014;Chelucci et al, 2015), although for sheep semen there are also controversial assessments (Fukui et al, 2008;Emamverdi et al, 2013). Many insemination organizations are hesitant to switch from the customary egg yolk to a phytoextender, because they are concerned that the latter may not be compatible with semen from all bulls and that, with the recently recommended substantial extension of the pre-freezing equilibration time, egg yolk seems to be indispensable.…”
Section: Discussionsupporting
confidence: 88%
“…Ele já foi testado por alguns pesquisadores (Muino et al, 2007), quando foi provada a viabilidade do uso desses para a congelação espermática (Janett et al, 2005). No entanto, outros autores não encontraram resultados positivos em relação à crioproteção espermática com o uso de diluidores livres de proteína animal (Nothling et al, 2007;Fukui et al, 2008).…”
Section: Introductionunclassified